CD4+ T cells expressing CX3CR1, GPR56, with variable CD57 are associated with cardiometabolic diseases in persons with HIV - Wanjalla, Celestine N.; Gabriel, Curtis L.; Fuseini, Hubaida; Bailin, Samuel S.; Mashayekhi, Mona; Simmons, Joshua; Warren, Christopher M.; Glass, David R.; Oakes, Jared; Gangula, Rama; Wilfong, Erin; Priest, Stephen; et al. (Frontiers in Immunology, 2023)
Persons with HIV (PWH) on long-term antiretroviral therapy (ART) have a higher incidence and prevalence of cardiometabolic diseases attributed, in part, to persistent inflammation despite viral suppression. In addition to traditional risk factors, immune responses to co-infections such as cytomegalovirus (CMV) may play an unappreciated role in cardiometabolic comorbidities and offer new potential therapeutic targets in a subgroup of individuals. We assessed the relationship of CX3CR1+, GPR56+, and CD57+/- T cells (termed CGC+) with comorbid conditions in a cohort of 134 PWH co-infected with CMV on long-term ART. We found that PWH with cardiometabolic diseases (non-alcoholic fatty liver disease, calcified coronary arteries, or diabetes) had higher circulating CGC+CD4+ T cells compared to metabolically healthy PWH. The traditional risk factor most correlated with CGC+CD4+ T cell frequency was fasting blood glucose, as well as starch/sucrose metabolites. While unstimulated CGC+CD4+ T cells, like other memory T cells, depend on oxidative phosphorylation for energy, they exhibited higher expression of carnitine palmitoyl transferase 1A compared to other CD4+ T cell subsets, suggesting a potentially greater capacity for fatty acid β-oxidation. Lastly, we show that CMV-specific T cells against multiple viral epitopes are predominantly CGC+. Together, this study suggests that among PWH, CGC+ CD4+ T cells are frequently CMV-specific and are associated with diabetes, coronary arterial calcium, and non-alcoholic fatty liver disease. Future studies should assess whether anti-CMV therapies could reduce cardiometabolic disease risk in some individuals.